2010
DOI: 10.1177/1938640010379635
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Successful Chopart Amputation in Patients With Diabetes

Abstract: Chopart amputations were first performed for treatment of a non-salvageable distal foot but became unfavorable because of the development of equinovarus contractures and ulcerations. The majority of below-knee amputations today occur in ambulatory patients with diabetes in which a Chopart amputation may be a viable option; however, the durability of the residual limb is questionable. The authors undertook a systematic review of electronic databases and other relevant sources to identify material relating to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Although this systematic review was performed by a single reviewer, the author has performed several systematic reviews with multiple reviewers and is well versed in the process of performing a systematic review. [12][13][14][15] All the included studies correlated with a low level of clinical evidence (level 4 and 5, therapeutic). No minimum postoperative follow-up time was set in the inclusion criteria in order to include as many studies as possible in the systematic review because of the paucity of the available literature.…”
Section: Discussionmentioning
confidence: 99%
“…Although this systematic review was performed by a single reviewer, the author has performed several systematic reviews with multiple reviewers and is well versed in the process of performing a systematic review. [12][13][14][15] All the included studies correlated with a low level of clinical evidence (level 4 and 5, therapeutic). No minimum postoperative follow-up time was set in the inclusion criteria in order to include as many studies as possible in the systematic review because of the paucity of the available literature.…”
Section: Discussionmentioning
confidence: 99%
“…They also saw that most complications or breakdowns occurred with ill-fitting devices or with unprotected ambulation. 27 …”
Section: Chopart Amputationmentioning
confidence: 97%
“…Regardless of the procedure and tendon balancing, success of Chopart amputations often relies on postoperative accommodation and bracing. 27,28 A systematic review looked at the literature associated with success of Chopart amputations and concluded that despite the osseous or tendinous procedures performed, a functional limb can be achieved with appropriate high-profile prosthetics. They also saw that most complications or breakdowns occurred with ill-fitting devices or with unprotected ambulation.…”
Section: Chopart Amputationmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful limb salvage, which was defined as a stump with functional ambulation, was seen in only 30 patients (67%) (14). A systematic review of the existing literature was conducted by Schade et al to identify any factors that may be associated with a successful Chopart amputation in diabetic foot problems (15). The efficacy of tendinous and/or osseous balancing could not be assessed due to lack of comparable techniques, highlighting the paucity of literature in this field (15).…”
Section: Distal or Minor Amputations For The Diabetic Footmentioning
confidence: 99%